2009
DOI: 10.1021/np900140s
|View full text |Cite
|
Sign up to set email alerts
|

Dracotanosides A−D, Spermidine Glycosides from Dracocephalum tanguticum: Structure and Amide Rotational Barrier

Abstract: Four new spermidine glycosides, dracotanosides A-D (1-4), have been isolated from Dracocephalum tanguticum. These molecules represent the first spermidine glycosides from this plant genus. The structures, including absolute configurations, were determined by spectroscopic and chemical methods. The amide bond rotational barrier of aglycone 1a was calculated by density functional theory (DFT) computation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…27,28) Polyamine alkaloids have a rich diversity of skeletons and biological activities. 21,34,35) The 13-membered ring moieties of 1 and 2 were a periphylline-type skeleton, and different from that of cyclic spermidine alkaloidal glycosides from M. urticifolia, which have a celacinnine-type skeleton. Periphylline and celacinnine had been isolated from Celastraceae plants.…”
Section: -21)mentioning
confidence: 93%
“…27,28) Polyamine alkaloids have a rich diversity of skeletons and biological activities. 21,34,35) The 13-membered ring moieties of 1 and 2 were a periphylline-type skeleton, and different from that of cyclic spermidine alkaloidal glycosides from M. urticifolia, which have a celacinnine-type skeleton. Periphylline and celacinnine had been isolated from Celastraceae plants.…”
Section: -21)mentioning
confidence: 93%
“…Previous studies on this plant revealed the presence of triterpenoids (Zhang et al, 1994;Li, 2006;Li and Jia, 2006;Zheng et al, 2007), steroids (Zhang et al, 1994;Li and Jia, 2006), flavonoids (Zhang et al, 1994;Li, 2006;Liu et al, 2009), alkaloids (Wang et al, 2009), lignans (Li, 2006), and coumarins (Zhang et al, 1994). In this paper, we report the isolation and structural elucidation of four new glycosides (1-4) from D. tanguticum, together with three known compounds: benzyl-β-D-glucopyranoside (5), 2-methoxy-4-(2-propen-1-yl)penyl-β-D-glucopyranoside (6), and pectolarigenin (7) (Fig.…”
Section: Introductionmentioning
confidence: 91%
“…Four spermidine alkaloid glycosides, dracotanosides A -D (218 -221, resp. ), were isolated from whole plant of D. tanguticum [43]. bovine brain-derived phospholipids against HO .…”
Section: Reviewmentioning
confidence: 99%